Nano vaccines for T. gondii Ribosomal P2 Protein With Nanomaterials as a Promising DNA Vaccine Against Toxoplasmosis - Yu, ZhengQing; He, Ke; Cao, WanDi; Aleem, Muhammad Tahir; Yan, RuoFeng; Xu, LiXin; Song, XiaoKai; Li, XiangRui (Frontiers in Immunology, 2022)
Caused by Toxoplasma gondii (T. gondii), toxoplasmosis has been aroused great threatens to public health problems around the world. So far, no effective vaccine or drug is commercially available, and the demands for the safe and effective therapeutic strategy have become more and more urgent. In the current study, we constructed a DNA vaccine encoding T. gondii ribosomal P2 protein (TgP2) and denoted as TgP2-pVAX1 plasmid. To improve the immunoprotection, nanomaterial poly lactic-co-glycolic acid (PLGA) and chitosan were used as the delivery vehicle to construct TgP2-pVAX1/PLGA and TgP2-pVAX1/CS nanospheres. Before vaccinations in BALB/c mice, TgP2-pVAX1 plasmids were transiently transfected into HEK 293-T cells and the expression of the eukaryotic plasmids were detected by laser confocal microscopy and western blot. Then the immunoprotections of naked DNA plasmids and its two nano-encapsulations were evaluated in the laboratory animal model. According to the investigations of antibody, cytokine, dendritic cell (DC) maturation, molecule expression, splenocyte proliferation, and T lymphocyte proportion, TgP2-pVAX1 plasmid delivered by two types of nanospheres could elicit a mixed Th1/Th2 immune response, and Th1 immunity as the dominant. In addition, TgP2-pVAX1/PLGA and TgP2-pVAX1/CS nanospheres functioned great advantages in enhancing immunity against a lethal dose of T. gondii RH strain challenge. All these results suggested that TgP2-pVAX1 plasmids delivered by PLGA or chitosan nanomaterial could be the promising vaccines in resisting toxoplasmosis and deserve further investigations and applications.